1996
DOI: 10.1111/j.1748-5827.1996.tb02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K deficiency in cats fed commercial fish‐based diets

Abstract: Clinical signs of vitamin K deficiency have been observed in cats offered two commercial canned diets high in salmon or tuna. Some of the queens and kittens offered these diets had died while survivors had increased coagulation times. Necropsies revealed hepatic and, or, gastrointestinal haemorrhages. Coagulation times of survivors returned to normal after vitamin K therapy. The purpose of this study was to induce a vitamin K deficiency in kittens and determine the dietary requirement. Kittens were offered vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Given the number of potentially hazardous ingredients found in commercial meat-based diets, it is not surprising that a significant number of controlled studies have demonstrated increased risks of a variety of diseases following long-term maintenance of cats and dogs on such diets, including kidney failure [ 71 ], liver, musculoskeletal, and neurologic diseases [ 72 ], birth defects [ 73 ], and bleeding disorders [ 74 ]. These have been described in more detail elsewhere [ 75 ].…”
Section: Health Of Omnivorous and Carnivorous Companion Animalsmentioning
confidence: 99%
“…Given the number of potentially hazardous ingredients found in commercial meat-based diets, it is not surprising that a significant number of controlled studies have demonstrated increased risks of a variety of diseases following long-term maintenance of cats and dogs on such diets, including kidney failure [ 71 ], liver, musculoskeletal, and neurologic diseases [ 72 ], birth defects [ 73 ], and bleeding disorders [ 74 ]. These have been described in more detail elsewhere [ 75 ].…”
Section: Health Of Omnivorous and Carnivorous Companion Animalsmentioning
confidence: 99%
“…It is possible to induce a vitamin K deficiency through diet, presumably as the cat is not particularly associated with coprophagic behavior. In an early study of queens and their kittens fed either a commercial tuna-or a salmon-based fish diet, there was a notable increase in blood clotting times [119]. Where the information is available, current commercial cat diets provide vitamin K 'activity' in the form of vitamin K3, principally in the dry food products.…”
Section: Feline Vitamin K Requirementsmentioning
confidence: 99%
“…36 Signs included the development of gastric ulcers, increased coagulation times, and decreased serum concentrations of vitamin K-dependent clotting factors. In two separate situations, cats fed canned commercial cat foods containing either salmon or tuna developed clinical signs of vitamin K deficiency.…”
Section: Vitamin Kmentioning
confidence: 99%